Deep eutectic solvent–based headspace single-drop microextraction for the quantification of terpenes in spices - Triaux, Zélie; Petitjean, Hugues; Marchioni, Eric; Boltoeva, Maria; Marcic, Christophe (Analytical and bioanalytical chemistry, 2020)
Deep eutectic solvents (DESs) were investigated as extracting solvent for headspace single-drop microextraction (HS-SDME). The extraction efficiency of 10 DESs mainly composed of tetrabutylammonium bromide (N 4444 Br) and long-chain alcohols was evaluated for the extraction of terpenes from six spices (cinnamon, cumin, fennel, clove, thyme, and nutmeg). The DES composed of N 4444 Br and dodecanol at a molar ratio of 1:2 showed the highest extraction efficiency and was selected to conduct the extractions of terpenes in the rest of the study. HS-SDME was optimized by design of experiments. Only two parameters from the four studied showed a significant influence on the efficiency of the method: the extraction time and the extraction temperature. The optimal extraction conditions were determined by response surface methodology. All extracts were analyzed by gas chromatography coupled to mass spectrometry (GC-MS). More than 40 terpenes were extracted and identified in nutmeg, the richest extract in terpenes in this study. Quantitative analysis based on 29 standards was conducted for each extract. Good linearity was obtained for all standards ( R 2 > 0.99) in the interval of 1 to 500 μg/g. Limits of quantification ranged from 0.47 μg/g (borneol) to 86.40 μg/g (α-farnesene) with more than half of the values under 2 μg/g. HS-SDME is simple, rapid, and cheap compared with conventional extraction methods. The use of DESs makes this extraction method “greener” and it was shown that DESs can be suitable solvents for the extraction of bioactive compounds from plants.